Dermatological manifestations of COVID 19 - Dawood Khan (Journal of Pakistan Association of Dermatologists, 2022)
Introduction COVID 19 (SARS 2 virus) was first isolated in China in December 2019 from the specimen of patients presented with lower respiratory tract infection. It was declared a global pandemic on March 11, 2020. Coronavirus disease 2019 infected patients can presents with different dermatological manifestations even in some cases; the dermatological manifestation may be the only presenting complaints of the patients. Objective To find dermatological manifestations in patients infected with COVID 19 virus. Methods After getting ethical approval from the hospital ethical and research committee, all the tested positive for SARS 2 virus were included in the study. Strict precautionary measures were taken according to the WHO guidelines. Patients having any chronic dermatological disease in the past or having more than two weeks duration of any dermatological illness were excluded. Photographs were taken from the patients having any dermatological manifestations. These photographs were then shared with the consultant dermatologists of the unit by hiding the course of clinical illness of the patients. The expert opinion of the consultant was considered as the final one. Results Mean age was 41,53 yearsÂ±1.6008E1 (3 months to 85 years) with 160 males (65.6%) and 84 females (34.4%). Pseudo chilblains, maculopapular rash, vesicular rash, and urticarial rash were noted in 13.9%, 15.6%, 4.9%, and 7%, respectively. Oral cavity erythema, ulcers, and erosions were noted in 25%, 11.9%, and 14.3% of patients. Based on gender, the p-value was significant for maculopapular rash (p=0.02) and oral petechiae (p=0.04), while based on age, the p-value was significant for urticarial rash (p=0.01) and vesicular rash (p=0.03). Conclusion COVID 19 is a severe form of viral illness with a fatal outcome. Dermatological manifestations may sometimes be the sole presenting complaints of the patients.